Syndrome of Inappropriate Antidiuretic Hormone Secretion and Cerebral/Renal Salt Wasting Syndrome: Similarities and Differences - Oh, Ji Young; Shin, Jae Il (Frontiers in Pediatrics, 2015)
Hyponatremia (sodium levels of < 135 mEq/L) is one of the most common electrolyte imbalances in hospital settings, especially in patients with neurologic diseases. Hyponatremia can cause cerebral edema and brain herniation and therefore, prompt diagnosis and proper treatment of hyponatremia is important in preventing morbidity and mortality. Among various causes of hyponatremia, the diagnosis of the syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt wasting syndrome (CSW) is still confusing due to many similarities between the SIADH and CSW. SIADH is caused by excess of renal water reabsorption through inappropriate antidiuretic hormone (ADH) secretion, and fluid restriction is the treatment of choice. Otherwise, CSW is caused by natriuresis, followed by volume depletion and negative sodium balance and replacement of water and sodium is the mainstay of treatment. Differentiation of these two diseases is difficult in most situations, because they overlap in many clinical and laboratory aspects. Although distinction between the SIADH and CSW is difficult, improvement of hypouricemia and an increased the fractional excretion of uric acid (FEUrate) after the correction of hyponatremia in SIADH, not in CSW may be one of the helpful points in discriminating the two disease. In this review, we compare these two diseases regarding the pathophysiologic mechanisms, diagnosis and therapeutic point of view.